From Louis Kahn to Rhino Vaults: the structural matrix of architectonic forms - Michela Barosio; Ludovica Rolando (Agathón)
The mismatch between the profiles of graduates and profiles required by the labour market has led the Politecnico di Torino to experiment with new forms of project’s teaching able to train professionals with markedly interdisciplinary profiles. Master’s Degree Programme Architecture Construction City gives shape to this interdisciplinary approach through the design units, which coordinate two to four disciplines around a single project. The experience of the Design Unit Architecture and Structural Forms is presented here as an example of this approach to the project through the recognition of the interrelation between the architectural and structural types and the coordinated use of physical and virtual models as a teaching tool.